Jawabanmu

2014-02-15T21:57:43+07:00
A)1 | 1   6     -5
            1     7    +
        1   7     2
b)2x-1 = 0
    2x   =1
      x  = 1/2
   1/2 | 2  21    -6     -5
               1     11    5/2   +
          2   22    5     -5/2

(x - 1/2) (2x² + 22x + 5) -5/2
(x - 1/2) 2 (x² + 11x + 5/2) -5/2
(2x -1) (x² + 11x + 5/2) -5/2
                 h(x)            s(x)

2. mempuyai faktor tersebut berarti persamaan itu apabila di bagi dengan x+3 harus = 0
   x³-3x²+Kx+6

-3 | 1    -3     K           6
           -3     18         -54-3K  +
      1    -6    18+K      0

berarti  -->   6 - 54 -3K = 0
                      -48 -3K = 0
                           -3K = 48
                               K = 48/-3
                               K = -16

maaf kalau salah :)